2017
DOI: 10.1007/s00264-017-3745-2
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of the Bryan cervical disc replacement: fifteen year follow-up

Abstract: In a cohort of 20 patients with 15-year clinical and radiological follow-up, the Bryan CTDR has demonstrated a sustained clinical improvement and implant mobility over time, despite a moderate progression of degenerative processes at the prosthetic and adjacent levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 31 publications
1
19
0
Order By: Relevance
“…A great variety of biomechanical studies have been published about cervical arthroplasty. Most studies focus on the ROM or on changes in disc height and facet translation compared with normal individuals and with patients after ACDF, or on clinical results [10][11][12][13][14][15][16][17][18][19][20][21][22]. Several studies also investigate qualitative motion of disc prostheses [1-9], but we did not nd studies investigating how the COR after insertion of a prosthesis compares with healthy individuals, which is important because our data shows that the COR in patients with disc herniations is not at a physiological position anymore and therefore the prae-op COR cannot be used as reference:…”
Section: Discussionmentioning
confidence: 99%
“…A great variety of biomechanical studies have been published about cervical arthroplasty. Most studies focus on the ROM or on changes in disc height and facet translation compared with normal individuals and with patients after ACDF, or on clinical results [10][11][12][13][14][15][16][17][18][19][20][21][22]. Several studies also investigate qualitative motion of disc prostheses [1-9], but we did not nd studies investigating how the COR after insertion of a prosthesis compares with healthy individuals, which is important because our data shows that the COR in patients with disc herniations is not at a physiological position anymore and therefore the prae-op COR cannot be used as reference:…”
Section: Discussionmentioning
confidence: 99%
“…14 Besides, mismatch between the prosthesis size and intervertebral space size is another prosthesis-related cause. 6 With respect to the patient-related causes, patients' underlying diseases, such as diffuse idiopathic skeletal hyperostosis, may predispose them to bridging bone developing in a scenario in which progression to ossification would not have occurred in most individuals. 16 Several theories have been proposed to explain the risk factors of SF after CDA.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 However, spontaneous fusion (SF), may also occur at the surgical segment as a rare complication of CDA. 6 Herein, we describe a rare case of SF following CDA and review related literature to identify its courses, risk factors, and preventive measures.…”
Section: Introductionmentioning
confidence: 99%
“…Dejaegher et al reported that 81% of the Bryan cervical disc remained mobile with a mean ROM of 8.6° at 8-year follow-up [ 7 ]. In addition, in a 15-year follow-up study of Bryan disc arthroplasty, Pointillart et al reported that 68.2% (15/22) of the prosthesis maintained mobile with an average of 9° at final follow-up [ 18 ]. Previous studies demonstrated that both CDA and ACDF had gained good long-term clinical outcome, and most of the cervical discs remained satisfactory segmental mobility [ 5 , 6 , 19 ].…”
Section: Discussionmentioning
confidence: 99%